Water, Soil, and Plants Interactions in a Threatened Environment - Gavrilescu, Maria (Water (Basel), 2021)
The unprecedented pressure posed by a growing population on water resources generates a significant shortage between the available resources and water demand, which together with water scarcity, floods, and droughts, can affect the world population and various other consumers. On the other hand, soil resources, which represent an essential and complex environmental ecosystem, as a support for the biological cycle, source of nutrients, and water for cultivated and wild plants, forestry, etc., are a provider of raw materials, and are increasingly degrading due to unsustainable use. Since both soil and water are vital resources and support for growth and life of plants, their preservation and sustainable management have become an urgent issue for policy makers, governmental factors, academia, and stakeholders. An important question to be answered is what the disturbing factors of soil–plants–water cycles are and how their negative influence can be reduced, since they affect the quality of life and human health. This work proposes an overview on new research into the links between soil and water, and the interactions among soil, water, and plants in a changing and threatened environment, which can determine human welfare. The analysis addresses the global context of water and soil resources, factors that affect their equilibrium and dynamics, especially toxic pollutants such as heavy metals and others, and their mutual relationship with plant growth.